Sinergi pembelajaran berbasis masalah dan motivasi berprestasi: membentuk kompetensi pemecahan masalah matematis siswa sekolah menengah kejuruan - Triyono, Didik; Gorky Sembiring, Maximus; Dwi Susandi, Ardi (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study evaluates the impact of Desmos-assisted Problem-Based Learning (PBL) compared to expository instruction on students' Mathematical Problem-Solving Ability (PSA) while accounting for varying levels of Achievement Motivation (AM) in vocational high schools. Design/methodology/approach: A quasi-experimental design was employed using Two-Way ANOVA. The sample comprised vocational students divided into experimental and control groups. Data were gathered through PSA tests and AM questionnaires. Findings: Desmos-assisted PBL significantly outperformed expository methods in enhancing PSA. Students with high AM demonstrated superior results. Crucially, no significant interaction was found between the teaching model and AM levels regarding PSA outcomes. Practical implications: Integrating Desmos into PBL serves as a robust pedagogical strategy for educators to bolster numeracy literacy and workforce readiness by fostering active cognitive engagement. Originality/value: This research contributes to the literature by integrating digital graphing tools (Desmos) within PBL frameworks specifically tailored to the vocational education context.   Purpose: Penelitian ini bertujuan membandingkan Kemampuan Pemecahan Masalah (KPM) matematis antara model Pembelajaran Berbasis Masalah (PBM) berbantuan Desmos dengan pembelajaran ekspositori, serta menganalisis pengaruh tingkat Motivasi Berprestasi (MB) terhadap KPM siswa SMK. Design/methodology/approach: Menggunakan desain quasi-experiment dengan analisis ANOVA Dua Arah. Sampel terdiri dari dua kelompok siswa SMK (eksperimen dan kontrol). Instrumen penelitian meliputi tes KPM dan angket MB. Findings: PBM berbantuan Desmos secara signifikan lebih efektif meningkatkan KPM dibanding model ekspositori. Siswa dengan MB tinggi mencapai skor KPM terbaik. Namun, tidak ditemukan interaksi antara model pembelajaran dan tingkat MB dalam memengaruhi KPM. Practical implications: PBM berbantuan Desmos terbukti sebagai strategi pedagogis efektif bagi guru SMK untuk meningkatkan literasi numerasi dan kesiapan kerja siswa melalui penguatan proses berpikir aktif. Originality/value: Studi ini memberikan kebaruan pada integrasi alat digital Desmos dalam sintaks PBM untuk mengatasi rendahnya KPM pada konteks pendidikan vokasi (SMK).